Halal vaccines: assessing the framework of mutanajjis and istihalah - Jamaludin, Mohammad Aizat; Hashim, Yumi Zuhanis Has-Yun; Rosli, Nur Liyana Izzaty (HH Publisher, 2025)
The discourse on Halal vaccines highlights the intersection of biopharmaceutical innovation and Islamic jurisprudence. Concerns over porcine-derived ingredients, Najis (impure) contamination, and the applicability of istihalah (transformation) have generated debates on vaccine permissibility in Muslim communities. This editorial examines the issues surrounding Halal vaccines through the framework of mutanajjis (contact with najis) and istihalah, assessing the implications for Halal status determination. A forward-looking approach that harmonizes scientific evidence with Shariah principles is essential for establishing global standards in Halal vaccine certification and fostering public confidence